The footprints of God - Iles, Greg.; Hill, Dick. (Grand Haven, Mich. : Brilliance Audio, 2003)
Appointed as ethicist to Project Trinity, Dr. David Tennant finds himself in a pressure cooker of groundbreaking science and colossal ambition. When a fellow scientist is murdered, David turns to Rachel Weiss, the psychiatrist probing the nightmares that have plagued him during his work at Trinity.
Compact disc.
Unabridged.
Read by Dick Hill.
Keywords: Technological innovations -- Fiction; Information technology -- Fiction; Medical ethics -- Fiction; Audiobooks; Suspense fiction